Development of a heptaplex PCR assay for identification of Staphylococcus aureus and CoNS with simultaneous detection of virulence and antibiotic resistance genes - Okolie, Charles Emeka; Wooldridge, Karl G.; Turner, David P.J.; Cockayne, Alan; James, Richard (BioMed Central, 2015)
Background Staphylococcal toxicity and antibiotic resistance (STAAR) have been menacing public health. Although vancomycin-resistant Staphylococcus aureus (VRSA) is currently not as widespread as methicillin-resistant S. aureus (MRSA), genome evolution of MRSA into VRSA, including strains engineered within the same patient under anti-staphylococcal therapy, may build up to future public health concern. To further complicate diagnosis, infection control and anti-microbial chemotherapy, non-sterile sites such as the nares and the skin could contain both S. aureus and coagulase-negative staphylococci (CoNS), either of which could harbour mecA the gene driving staphylococcal methicillin-resistance and required for MRSA-VRSA evolution.